Social knowledge creation in the complex responsive processes theory - Ćwiklicki, Marek (Journal of Public Governance, 2013)
The aim of the paper is to explain social knowledge creation in terms of the Complex Responsive Processes (CRP) theory. As a methodological framework of his analysis, the author gives a detailed description of the CRP approach, presents the phenomena of learning and knowledge creation in an organizational context, and considers the social level of knowledge. He discusses contributions by J. Hausner, J. Górniak, S. Mazur, and A. Giza, who embed the problem of knowledge in the social context that is covered in the current issue of the journal. In his conclusion, the author assesses the interpretation of social knowledge on the basis of the CRP assumptions and offers some thoughts on the end limits and future directions of this approach.